Estimation of mRNA levels of interleukin (IL)-10, tumor necrosis factor (TNF)-α, IL-4 and interferon (IFN)-γ in HIV infected children in Mumbai - Kothari, Sweta T. (Springer India, 2006)
Cytokines, viral load and opportunistic infections play an important role in HIV-disease progression. Hundred children vertically infected with HIV were enrolled to determine mRNA levels of TNF-α, IL-10, IL-4 and IFN-γ. These levels were estimated by amplifying cytokine mRNA from peripheral blood mononuclear cells. Severity of HIV was staged by the reduction in CD(4)(+) T cells and the onset of opportunistic infections. IL-10 mRNA levels were observed to increase with the severity. Despite the rising IL-10 mRNA levels, TNF-α mRNA levels increased with severity of HIV and decrease in CD(4)(+) T cell counts. IL-4 mRNA levels increased with the reduction in CD(4)(+) T cell numbers. Depleting mRNA levels of IFN-γ contributed to the worsening of HIV disease. Increase in TNF-α and IL-4 levels appended to the disease severity by upregulation of the viral replication. Increased IL-10 levels and decreased IFN-γ levels predisposed the children to HIV associated opportunistic infections, which in return contributed to cytokine disarray.